2020
DOI: 10.31436/imjm.v17i3.244
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Barriers to Exercise in Women with Gestational Diabetes Mellitus

Abstract: Introduction: Good control of glycaemia negates potential maternal and fetal complications. A diet suitable for women with gestational diabetes mellitus (GDM) is a first line approach. However, little is said about suitable exercise in pregnancy that will potentially help control glycaemia. This pilot study seeks to understand the perceived barriers to exercise in women with GDM. Materials and Methods: This crosssectional study recruited patients with GDM on diet control at the antenatal clinic of Hospital Sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Physical interventions have also been explored in Southeast Asia [104][105][106]. High levels of physical activities, particularly moderate-intensity activities and household/caregiving activities during pregnancy, were associated with a lower prevalence of GDM independent of sitting time [106].…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical interventions have also been explored in Southeast Asia [104][105][106]. High levels of physical activities, particularly moderate-intensity activities and household/caregiving activities during pregnancy, were associated with a lower prevalence of GDM independent of sitting time [106].…”
Section: Managementmentioning
confidence: 99%
“…Padmapriya et al [104] associated it with lower two-hour plasma glucose levels, particularly in overweight/obese women. However, factors such as tiredness, childcare duties, and lack of time were perceived barriers to exercise in women with GDM [105]. The researchers suggested that health care professionals' involvement in educating women with GDM on exercise can promote awareness.…”
Section: Managementmentioning
confidence: 99%
“…Despite this national guidance, the promotion of PA is an underutilised management tool. This pattern is reported globally, a recent report from Brazil found that at least 65% of women with GDM are not meeting PA recommendations [ 11 ] and only a small proportion (6.7.%) were using healthcare professionals as their source of information on exercise in pregnancy [ 12 ]. Qualitative reports have found that women with GDM would prefer clear, simple and specific PA messages with flexible options [ 13 ].…”
Section: Introductionmentioning
confidence: 63%
“…overprotective) (+/) Interaction with other pregnant women Home responsibilities; caring for child or partner limits PA opportunities (−) Negative pressure/culture from family leads to avoidance of PA (−) Social influences (Process that can change thoughts feelings or behaviours – social pressure) Individuals confident with PA programmes Support from HCP Physical opportunity Lack of access to physical activity/leisure (facilitates) (−) Lack of outdoor space to be space (−) Lack of time (childcare/work commitments) (−) Environmental context and resources (persons situation or environment) Time, resources and location influence PA choice, affecting behaviour. Reflective motivation Belief about capacity ‘time for change’ particularly for the benefit of the baby’) (+) PA is associated with feeling of guilt or frustration/concerns due to reduce capacity compared to pre-pregnancy, which leads to avoidance of PA (−) Feeling responsible (+) Beliefs about capability (acceptance of the truth, reality or validity about an ability, perceived behavioural control, self-esteem, confidence) Self-efficacy influences approach to PA. Belief about capability toward PA Increased self-monitoring and feedback Recognition of improvements through self-monitoring and feedback leads individuals to recognise their capabilities and increase motivation for PA (+) Goals Belief that PA is enjoyable and leads to health benefits (+) Self-efficacy: activity may lead to harm & avoidance of PA (due to health beliefs) Belief about consequences Automatic motivation PA is associated with discomfort/pain, which leads to avoidance of PA (−) (due to negative emotions associated activity) Establishing a routine (+) and maintaining habits after (+) are important in the maintenance of PA Pre-pregnancy PA habits (+/−) Apprehensive of PA in public place (−) Fear/anxiety based on previous pregnancy/miscarriage _(−) Emotion Habits and routines influence behaviour Abbreviations : PA Physical Activity, TDF Theoretical Domains Framework, GDM Gestational Diabetes, HCP Health care professionals a Barrier and enablers drawn from both focus group and current literature [ 12 , 13 , 37 – 41 ] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation